Damage detection in adhesively bonded single lap joints by using backface strain: Proposing a new position for backface strain gauges. (March 2020) - Sadeghi, M.Z.; Weiland, J.; Preisler, A.; Zimmermann, J.; Schiebahn, A.; Reisgen, U.; Schroeder, K.U.
Abstract: The application of adhesively bonded components is increasing in the lightweight design particularly in aerospace. However, the lack of easy and reliable techniques for the assessment of structural integrity of such components while they are in service, increases the number of periodic inspections. The present work proposes a location for positioning the back-face strain gauge on the adhesively bonded single lap joints (SLJs) for damage detection. This location is based on the healthy (undamaged) state of the joint and is independent of the applied load. In SLJs, the interaction of the positive strain due to the applied load and the negative strain induced by the bending moment, forms a point with zero strain on the back-side of the adherent. This point can be considered as the damage indicator since with the propagation of the crack the so-called zero strain point gains strain. The proposed position for the back face strain gauges was showed high potential as damage indicator in adhesively bonded SLJs.